Hubungan Antara Elemen-Elemen Budaya Organisasi, Kepuasan Kerja Dan Sistem Kerja Berpasukan Di Kalangan Staf Sokongan Bank Pertanian Malaysia - Ab. Rahim, Ab. Hamid (2002)

(untitled)
The purpose of this study is to determine the relations and the influences of organizational culture on the job satisfaction and group functioning among the supporting staff of Bank Pertanian Malaysia. 65 supporting staff who attached to the Bank Pertanian Malaysia Penang State became the subject of the study. Data obtained by using questionnaires that contained items which were suggested by past researchers. Descriptive and inference statistic tests were used to analyze the data. The results of the study showed that job design significantly related to the job satisfaction and the peer leadership significantly related to the group functioning.